2010
DOI: 10.1007/s00347-009-2063-5
|View full text |Cite
|
Sign up to set email alerts
|

Glaukom und Keratoplastik

Abstract: Glaucoma and corneal disorders are often associated and are of diagnostic, therapeutic and prognostic relevance for each other. Glaucoma is already present in approximately 15% of eyes prior to keratoplasty, whereas in addition approximately 15% of cases are diagnosed following corneal transplantation. Corneal opacities, surface irregularities and pachymetric deviations from the norm can have a negative impact on tonometry, perimetry and morphological glaucoma diagnosis. Digital and intracameral tonometry as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…In posterior lamellar keratoplasty these risk factors are avoided, which may explain the lower rate of postoperative glaucoma after these procedures reported so far. 6 In a group of 1122 PK eyes, Kirkness and Ficker 21 found that 14% developed a manifest glaucoma postoperatively. So far the reported fractions of eyes developing glaucoma after posterior lamellar keratoplasty are highly variable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In posterior lamellar keratoplasty these risk factors are avoided, which may explain the lower rate of postoperative glaucoma after these procedures reported so far. 6 In a group of 1122 PK eyes, Kirkness and Ficker 21 found that 14% developed a manifest glaucoma postoperatively. So far the reported fractions of eyes developing glaucoma after posterior lamellar keratoplasty are highly variable.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 In approximately 15% of cases a manifest glaucoma develops after PK. 6 This prevalence is described to be as low as 3% after posterior lamellar keratoplasty. 7 It was our aim to analyze trabecular meshwork outflow facility before and after posterior lamellar keratoplasty to find out whether it was significantly altered by the surgical techniques utilized.…”
mentioning
confidence: 98%
“…Additionally, one critical point of analysing data after PK and after DSEK is the measurement of IOP [19,56,57,58]. Corneal irregularity and increased corneal thickness may influence the validity of applanatory pressure measurement, especially in eyes with BK.…”
Section: Discussionmentioning
confidence: 99%
“…Ââåäåíèå. Óðîâåíü îôòàëüìîòîíóñà ó áîëüíûõ ñ áåëüìàìè è ïîñëå êåðàòîïëàñòèêè ÿâëÿåòñÿ âàaeíûì äèàãíîñòè÷åñêèì êðèòåðèåì ïðè îöåíêå ãèäðîäèíàìèêè [1,5,7,10]. Íàèáîëåå ðàñïîñòðà-íåííûìè ÿâëÿþòñÿ ðîãîâè÷íûå ìåòîäû èçìåðåíèÿ âíóòðèãëàçíîãî äàâëåíèÿ (ÂÃÄ).…”
unclassified